Mediating Role of Affective Commitment in The Effect of Ethical Work Climate on Felt Obligation Among Public Officers - Pradesa, Hafid Aditya; Dawud, Joni; Affandi, Muhamad Nur (University of Islam Malang, 2019)
Social exchange theory (SET) which explains the terms of the exchange agreement under the psychological contract assumes that what was promised is a key point in explaining individual responses at work. It was climate and support which will be argued as antecedents of individuals' attitudes and behaviors. Along with organizational support, ethical work climate was mostly examined only in relationship with intent-to leave. The purpose of this study was to determine felt obligation as the attitudinal outcome of ethical work climate, perceived organizational support, and affective commitment in terms of social exchange mechanism. This study is explanatory research based on primary data with a survey as the data gathered method. The result shows that one of five hypotheses rejected in this study. Furthermore, ethical work climate and perceived organizational support could affect felt obligation through affective commitment as mediation. Our findings are discussed below by considering the implications and limitations of this study.